CREATIVE WRITING AS AN ALTERNATIVE TO CONTEMPORARY JOURNALISM - Domazet, Sanja; Sanja, (Political Review, 2024)
Nedeljnik belongs to the type of the most modern weekly press in Serbia. In the crisis of the print media time, it has been surviving on the market for more than a decade and creating a new, creative public by placing texts created in creative writing. This magazine introduces new journalistic practices and genres by combining journalistic and literary techniques. Literary journalism is represented in journalistic texts and the works of writers. Nedeljnik is the best indicator that literary journalism can survive in the digital age. As well is also at a time when the audience is mostly informed on the Internet and looking for more entertaining and less educational texts.
Keywords: creative writing; literary language; weekly press; literary journalism; journalistic genres